Exploring science through art - Katz, Phyllis, 1946- (New York : F. Watts, 1990)
Demonstrates how many forms existing in art are taken from natural phenomena and suggests art projects using simple motifs from nature.
Includes bibliographical references (p. 60-61) and index.
Keywords: Art and science -- Juvenile literature; Nature (Aesthetics) -- Study and teaching -- Juvenile literature; Art -- Study and teaching (Elementary) -- Juvenile literature; Science -- Study and teaching (Elementary) -- Juvenile literature; Art and science; Nature (Aesthetics)